2012
DOI: 10.1007/s00280-012-1881-3
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of proton pump inhibitors or H2 blockers did not adversely affect nilotinib efficacy in patients with chronic myeloid leukemia

Abstract: Purpose The impact of proton pump inhibitors (PPIs) and histamine H2 receptor antagonists (H2 blockers) on the efficacy of nilotinib was evaluated. Methods Retrospective analyses were performed in patients with newly diagnosed Philadelphia chromosome-positive (Ph+) chronic myeloid leukemia in chronic phase (CML-CP; N = 492) and in patients with imatinib-resistant or -intolerant Ph+ CML-CP (N = 256) treated with nilotinib. Results In the newly diagnosed population, 87 (17.7%) and 49 (10.0%) patients receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In addition to the findings of Yin et al 11 and Severino et al 10 studies with PPIs have demonstrated relevant in vitro interactions at clinically achievable concentrations, which have resulted in a 20% elevation in digoxin levels 6 as a result of ABCB1 inhibition. These interactions may also be exacerbated by cytochrome P450, CYP2C19 variant alleles, which impact significantly on the metabolism of PPIs.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In addition to the findings of Yin et al 11 and Severino et al 10 studies with PPIs have demonstrated relevant in vitro interactions at clinically achievable concentrations, which have resulted in a 20% elevation in digoxin levels 6 as a result of ABCB1 inhibition. These interactions may also be exacerbated by cytochrome P450, CYP2C19 variant alleles, which impact significantly on the metabolism of PPIs.…”
mentioning
confidence: 82%
“…In a more recent paper, Yin et al 11 have demonstrated a modest superiority in the rate of major molecular response (MMR; reduction in BCR-ABL% (the % BCR-ABL relative to the control gene BCR, measured by quantitative reverse transcriptase PCR) to a level p0.1% International Scale (IS)) in patients treated with nilotinib and PPIs compared with that observed in patients receiving nilotinib alone (MMR rate at 12 months: nilotinib 300 mg b.i.d. with PPIs or H2 blockers 49.6% vs nilotinib alone 41%).…”
mentioning
confidence: 98%
“…The effect of concomitant administration of proton pump inhibitors in patients receiving nilotinib has been recently investigated, with no adverse effect of TKI efficacy described; in fact, a modest yet statistically insignificant improvement in patient response was observed. 41 In keeping with these observations, our laboratory has demonstrated in vitro that proton pump inhibitors significantly increase the intracellular concentration of nilotinib both in cell lines and in primary patient cells. 22,42 Accordingly, administration of concomitant therapies with well-documented safety profiles may enhance the effects of TKIs through inhibition of efflux transporters.…”
Section: Inhibition Of Abcb1 and Abcg2mentioning
confidence: 69%
“…Proton pump inhibitors, such as pantoprazole and esomeprazole, are frequently prescribed to CML patients to alleviate gastric side effects experienced as a result of TKI therapy or for attendant comorbidities. The effect of concomitant administration of proton pump inhibitors in patients receiving nilotinib has been recently investigated, with no adverse effect of TKI efficacy described; in fact, a modest yet statistically insignificant improvement in patient response was observed 41 . In keeping with these observations, our laboratory has demonstrated in vitro that proton pump inhibitors significantly increase the intracellular concentration of nilotinib both in cell lines and in primary patient cells 22 , 42 .…”
Section: Inhibition Of Abcb1 and Abcg2mentioning
confidence: 85%
“…The robustness and consistency of the results were further demonstrated with analyses based on different cutoffs of concomitant usage of PPIs with ceritinib treatment at 30, 50, 70, and 90% of the time (data on file). A similar approach has been applied to other compounds such as nilotinib [26] and idelalisib [27], in which patients need to be on PPIs for ≥50% of the time while on treatment with these compounds to assess PPI effect on their exposure. The results from this analysis suggest that the concomitant use of PPIs did not affect the steady-state PK in ALK-positive patients.…”
Section: Discussionmentioning
confidence: 97%